Unterwegs - Mobiles Leben in der Erdgas- und Erdölindustrie in Russlands Arktis - Saxinger, Gertrud (2016)
Barely known in public is the life of long-distance commute workers who extract the "blue and black gold" for the export to Europe. They are travelling people who work and live rotationally for a few weeks at the extraction sites before they go back again to their families in the southern regions. This ethnography takes the reader from the Volga Region to the Arcitc "Russian Gas Capital" Novy Urengoy and provides critically insights into the Russian petroleum industry.